2007
DOI: 10.1016/j.cardiores.2006.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes mellitus attenuates the repolarization reserve in mammalian heart

Abstract: It is concluded that type 1 diabetes mellitus, although only moderately, lengthens ventricular repolarization, attenuates the repolarization reserve by decreasing I(to) and I(Ks) currents, and thereby may markedly enhance the risk of sudden cardiac death.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
86
2
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(94 citation statements)
references
References 53 publications
(62 reference statements)
5
86
2
1
Order By: Relevance
“…This work is performed in an animal model (rat) which has only part of the cardiac K + repolarizing currents present in human heart (I to and IK 1 ). Different works carried out in different animal models showed that IK 1 is not affected by diabetes, IK s is slightly reduced, IK r is slightly or no reduced, and I to is reduced by half, being this last the main responsible for the action potential alterations found in diabetic hearts [2,14,40,41]. However, based on the results obtained with I to , we can expect that the intracellular regulation of the other channels would be impaired in diabetic hearts as well.…”
Section: Discussioncontrasting
confidence: 39%
“…This work is performed in an animal model (rat) which has only part of the cardiac K + repolarizing currents present in human heart (I to and IK 1 ). Different works carried out in different animal models showed that IK 1 is not affected by diabetes, IK s is slightly reduced, IK r is slightly or no reduced, and I to is reduced by half, being this last the main responsible for the action potential alterations found in diabetic hearts [2,14,40,41]. However, based on the results obtained with I to , we can expect that the intracellular regulation of the other channels would be impaired in diabetic hearts as well.…”
Section: Discussioncontrasting
confidence: 39%
“…However, the demonstration that genetic variants in NOS1AP reproducibly alter QT interval duration in families aggregating diabetes demonstrates that genetic effects are not swamped out by the strong effect of diabetes on repolarization. Rather, the opposite appears to be true: the reduced repolarization reserve of diabetes (35,36) shows a synergistic interaction with genetic variants that alter myocardial repolarization. It is thus notable that the strength of the effect of NOS1AP SNPs in EuropeanAmerican diabetic subjects in the current report, 11.3-to 13.9-ms differences between alternate homozygotes, is much greater than that observed in the previous reports by Arking et al (11) Of additional interest, 34% (n ϭ 264) of all European-American diabetic subjects (n ϭ 778) in the Diabetes Heart Study is using a QT-altering medication (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes is known to induce marked remodelling in the set of cardiac ion currents in all mammalian species studied, including dogs (Lengyel et al, 2007), rabbits (Lengyel et al, 2008) and rats (Magyar et al, 1992). In addition, differences in the effects of both rosiglitazone and troglitazone were observed when compared between healthy and diabetic rats (Arikawa et al, 2002;Kavak et al, 2008).…”
Section: Limitations Of the Studymentioning
confidence: 95%